Spatial coordination between chromosomes and cell division proteins in Escherichia coli - Männik, Jaan; Bailey, Matthew W. (Frontiers in Microbiology, 2015)
To successfully propagate, cells need to coordinate chromosomal replication and segregation with cell division to prevent formation of DNA-less cells and cells with damaged DNA. Here, we review molecular systems in Escherichia coli that are known to be involved in positioning the divisome and chromosome relative to each other. Interestingly, this well-studied micro-organism has several partially redundant mechanisms to achieve this task; none of which are essential. Some of these systems determine the localization of the divisome relative to chromosomes such as SlmA-dependent nucleoid occlusion, some localize the chromosome relative to the divisome such as DNA translocation by FtsK, and some are likely to act on both systems such as the Min system and newly described Ter linkage. Moreover, there is evidence that E. coli harbors other divisome-chromosome coordination systems in addition to those known. The review also discusses the minimal requirements of coordination between chromosomes and cell division proteins needed for cell viability. Arguments are presented that cells can propagate without any dedicated coordination between their chromosomes and cell division machinery at the expense of lowered fitness.